The centralist decentralization of Peru: between crisis and development 1970-2014 - Miranda Valdivia, Franklin Ramiro (2015)
Peruvian centralism extends social and economic inequalities and the urban and regional disparities as well as increase the income disproportions compared to other countries. It is also important to note that the development model and type of centralist state in the twentieth century have seriously impacted the disintegration, inequality and migration from the provinces. Also the rural social movements, migration of young people, accelerated aging of its population contributed to the dislocation and impoverishment of the provinces. The lack of a modern political class and with regional, national and decentralist inspiration has made that the Peruvian development consolidates mostly in the axis of the coast of the country and particularly in Lima. The dimensions of centralism are economic, demographic, territorial, ethnic-linguistic and social political. Is not possible to understand the development process without considering the natural and historical territorial space that are concerned and how caring and exploit these spaces that watersheds. One of the fundamental aspects of national development is the existence of a modern, democratic, decentralized state with a political class with legitimacy.